The relations between different components of intolerance of uncertainty and symptoms of depression during the COVID-19 pandemic: A network analysis - Feng, Tingwei; Ren, Lei; Liu, Chang; Li, Kuiliang; Wu, Lin; Wei, Xinyi; Yuan, Shangqing; Cui, Long-Biao; Yang, Xi; Li, Danyang; Yang, Wei; Li, Ye; et al. (Frontiers in Psychiatry, 2022)
Background: The relations between depression and intolerance of uncertainty (IU) have been extensively investigated during the 2019 coronavirus disease (COVID-19) pandemic. However, there is a lack of understanding on how each component of IU may differentially affect depression symptoms and vice versa. The current study used a network approach to reveal the component-to-symptom interplay between IU and depression and identify intervention targets for depression during the COVID-19 pandemic. Methods: A total of 624 college students participated in the current study. An IU-Depression network was estimated using items from the 12-item Intolerance of Uncertainty Scale and the Patient Health Questionnaire-9. We examined the network structure, node centrality, and node bridge centrality to identify component-to-symptom pathways, central nodes, and bridge nodes within the IU-Depression network. Results: Several distinct pathways (e.g., “Frustration when facing uncertainty” and “Feelings of worthlessness”) emerged between IU and Depression. “Fatigue” and “Frustration when facing uncertainty” were identified as the central nodes in the estimated network. “Frustration when facing uncertainty”, “Psychomotor agitation/retardation” and “Depressed or sad mood” were identified as bridging nodes between the IU and Depression communities. Conclusions: By delineating specific pathways between IU and depression and highlighting the influential role of “Frustration when facing uncertainty” in maintaining the IU-Depression co-occurrence, current findings may inform targeted prevention and interventions for depression during the COVID-19 pandemic.